2014
DOI: 10.1021/jp4119343
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Effective Medium Theory to Extract the Optical Properties of Two-Dimensional Nonspherical Metallic Nanoparticle Layers

Abstract: International audienceA new effective medium theory is introduced to describe the optical properties of a two-dimensional array of metallic nanoislands. This model which takes into account both the nanoisland orientation and their shape distribution is successfully used to interpret the ellipsometric measurements performed on gold nanoislands sputtered on a silicon substrate. By coupling ellipsometry to atomic force microscopy measurements, we show that the growth mechanism involves a Volmer-Weber growth mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…17,18 However, preparation routes unavoidably conduct to NPs showing a shape distribution which induces drastic changes in the optical properties of NP assembly. [19][20][21][22] Indeed, by combining Gibbs free energy calculation to discrete dipole approximation, Noguez et al [23][24][25] have shown that the morphology and so the optical properties of NPs depend on the temperature used to synthesize them. In addition, as reported by Sayah et al, 19 silver prolates grown in a mesoporous silica matrix exhibit a large length distribution which induces an inhomogeneous broadening of the L-SPR bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, preparation routes unavoidably conduct to NPs showing a shape distribution which induces drastic changes in the optical properties of NP assembly. [19][20][21][22] Indeed, by combining Gibbs free energy calculation to discrete dipole approximation, Noguez et al [23][24][25] have shown that the morphology and so the optical properties of NPs depend on the temperature used to synthesize them. In addition, as reported by Sayah et al, 19 silver prolates grown in a mesoporous silica matrix exhibit a large length distribution which induces an inhomogeneous broadening of the L-SPR bands.…”
Section: Introductionmentioning
confidence: 99%
“…Another two dimensional effective medium theory was recently introduced to analyse ellipsometric measurements performed on gold nanoisland films. 20 This theory takes into account both the shape distribution of oblate nanoislands and the anisotropy induced by their two dimensional orientation. However, this model neglects charge image effects.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was used to design broadband epsilon-near-zero composites, 20 and to interpret ellipsometric measurements performed on gold nanoisland films. 21 However, this model only considers a distribution of depolarisation factor of NPs and fails to extract directly the NP aspect ratio.…”
mentioning
confidence: 99%
“…140 The slightly weaker insulating properties of the gold NPs film for the inplane polarization (TE) are understandable since the dipole coupling between the gold NPs should occur first for in-plane polarization and help the gold film tend toward metallic material as the film grows. 147 However, the significant differences in the birefringence and absolute values of the measured effective medium results as a function of SRI are unexpected and may reveal new and important effects that occur near the insulator-to-metal transition of gold at these thicknesses and wavelengths.…”
Section: Discussionmentioning
confidence: 97%
“…In the EMA models, the gold aggregates are represented by point dipoles embedded in the homogenous background, and the resulting effective permittivity of the mixture is dependent on the complex permittivities of the two constituents (gold and surrounding material), and on the volume fraction of gold. For experimental studies of thin gold films, spectroscopic ellipsometry is one of the most common measurement tools as it is highly sensitive to the optical properties of thin films 140,[145][146][147]. However, most of the previous work in this area was focused on measuring the thickness-dependent complex permittivity calculated from the ellipsometric angles to investigate the effect of various thin film growth mechanisms, including the impact of the shape and distribution of the NPs making up the ultrathin films.…”
mentioning
confidence: 99%